Rewriting democracy: cultural politics in postmodernity - Ermarth, Elizabeth Deeds (ed.) (Aldershot, 2007)
Illuminating and comprehensive, this excellent volume addresses the problematic relationship between democratic institutions and the current critique of enlightenment and modernity. Since at least the beginning of the twentieth century, and across the range of practice from science to politics to art, various cultural shifts have unsettled assumptions that have been fundamental to the development of democratic institutions: assumptions concerning individual identity, the nature of political systems, and the viability of egalitarian ideals. Can democracy survive these changes to the value systems upon which it has been based for over two centuries? This study does not focus on the often repeated particulars of past or current events such as 9/11 or the genocide in Darfur, but instead examines the terms and conditions under which it would be possible to prevent such events in the future.
Keywords: Democracy